Modelagem de equações estruturais para analisar a estratégia corporativa sustentável: estudo em empresas que atuam no Brasil - Torres, Franklin de Sousa (2011)
The main aim of this dissertation was evaluate the relationship between the components factors of the sustainable corporative strategy model, based on Abreu's SCP-Triple (2001). The discussions on environment and social worry of the companies and the feedback they owe to their different stakeholders take us to new considerations on the models recently presented. Abreu (2001) faced with the need of evaluate the strategy used by the company, not only in the economic dimension, but also social and environmental, proposed the Triplice Strategy Evaluation Model, called SCP-Triple (Structure, Conduct and Performance). Opposing the SCP model, that emphasizes only the economic dimension as the performance aspect. The SCP-Triple also include the social and environmental aspects.